Universal Fabrication of 2D Electron Systems in Functional Oxides. Issue 10 (11th January 2016) - Rödel, Tobias Chris; Fortuna, Franck; Sengupta, Shamashis; Frantzeskakis, Emmanouil; Fèvre, Patrick Le; Bertran, François; Mercey, Bernard; Matzen, Sylvia; Agnus, Guillaume; Maroutian, Thomas; Lecoeur, Philippe; Santander‐Syro, Andrés Felipe
Abstract : 2D electron systems (2DESs) in functional oxides are promising for applications, but their fabrication and use, essentially limited to SrTiO3 ‐based heterostructures, are hampered by the need for growing complex oxide overlayers thicker than 2 nm using evolved techniques. It is demonstrated that thermal deposition of a monolayer of an elementary reducing agent suffices to create 2DESs in numerous oxides.